Krisis Relevansi Balāghah dalam Pembelajaran Bahasa Arab: Sebuah Literature Review Berbasis Analisis Tujuan Instruksional - Ghazi, Fachrul (Jurnal Intelek Insan Cendikia, 2025)
This literature review research analyzes the relevance crisis of balāghah in Arabic language learning through an instructional objectives analysis approach. The research method used is a systematic literature review of 50 articles from SINTA and Scopus indexed journals published between 2015-2024. The findings reveal three main aspects of the crisis: first, a significant gap between the classical objectives of balāghah (production of eloquent speech) and modern instructional objectives that emphasize communicative competence and functional language skills; second, the marginalization of balāghah in contemporary Arabic language curricula, with allocation of less than 10% of total instructional time in most institutions; third, pedagogical problems including conventional teaching methods, abstract materials, and assessment focused on theoretical mastery rather than practical application. Factors contributing to this crisis include the dominance of structural linguistics paradigms, limited teacher competence in applied balāghah, and the pressure of market-oriented educational demands. The study concludes that balāghah reconstruction is needed by reorienting its instructional objectives toward pragmatic and functional dimensions, integrating it with modern language skills, and developing contextual teaching materials based on contemporary discourse analysis. This research recommends the development of a new balāghah curriculum framework that bridges classical tradition with modern communicative needs, along with comprehensive teacher training programs.